Europe 2020 Strategy, Cohesion Policy and Greek Regions: Are we "smart" enough? - Yiannis Saratsis; Angelos Kotios (European Regional Science Association (ERSA), 2011)
Since the beginning of 2010, European Commission has launched the new strategic framework for Europe, which is now known as the "Europe 2020 Strategy". This new strategy has been set as the successor of the so called "Lisbon-Gothenburg Strategy" which was set in early '00 as the strategy for Europe in the 21st century. Actually the two strategies have a lot in common. The main driving forces of Europe still remain the same and some rearrangement in the EU-wide strategic targets has been made. Of course the economic crisis that has emerged forced for a new priority that was set in the "EU 2020" strategy, but the main targeting still encompasses the three corners of the well known sustainability triangle, namely economy, environment and society. The setting of a new strategy arises some questions. Why does Europe need a new development strategy? Was the old strategy successful or not? Was every country in Europe adapted in the old strategy properly? Where there any problems in the implementation of the old strategy? What was the overall outcome of the old strategy in EU Level, in each Member State and in the regions of Europe? Is the new strategy better adjusted to cope with the development problems in European, national and regional level? Furthermore, European Commission has already asked MS to comply with the specifications of the "Europe 2020 Strategy" in the planning and implementation of the Cohesion Policy's programs in the following years (for the remaining of the 2007 - 2013 period and especially for the 2014-2020 period). This article discusses the above questions and tries to find answers on the rationale and prospects of the new strategy. Also, in a second step we give more emphasis in Greece and Greek Regions that have been not well adapted in the "Lisbon Strategy" as shown in the recent 5th Cohesion Report and other studies. Finally, the article closes with policy recommendations regarding the consistency and interaction between the "Europe 2020 Strategy" and Cohesion Policy, and also some policy recommendations for Greek regional policy and Greek regions.
Keywords: 330